Development of the Republic of Sakha (Yakutia)'s Shadow Economy Assessment Methodology - Karatayeva, Tamara A.; Danilova, Elena V.; Parfenova, Olga T.; Evseev, Prokopiy V.; Kampeeva, Elena E. (International Journal of Criminology and Sociology, 2022)
The purpose of the article is to study the shadow economy assessment methodology. This article presents a comprehensive study of the parameters of a shadow economy, considers its essence, and defines its terminology. This study outlines the historical approach to the development of the shadow economy, both in Russia and worldwide, and gives a brief analysis of the economy of the Republic of Sakha. The authors examined the specifics of the statistical methods applied in assessing various structural elements of a shadow economy and measured and assessed the shadow economy in this region. The research conducted enabled the authors to formulate the main measures required to reduce the shadow economy. The scientific novelty is justified by the research results, which included studying and summarizing a wide range of published and unpublished materials, the examination of the initial and transitional periods of the shadow economy development in Yakutia. The article reveals the main causes and conditions that lead to the formation of the shadow economy in various sectors of the Yakutia economy. The solutions and suggestions proposed in the article are aimed at reducing the shadow economy parameters. The scientific research results are of theoretical and applied importance for public administration and authorities to improve the effectiveness of the fight against the shadow economy manifestations.